Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada MIXUE Ice Cream & Tea - Putri Amanda; Natal Indra (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to find out how much influence product quality and service quality have on customer satisfaction at Mixue Ice Cream & Tea. The research method used is a quantitative method approach with data collection techniques using non-probability sampling with a population of 100 respondents and samples taken using the Slovin formula, namely 50 respondents. Data collection used a questionnaire on a Likert scale. Data processing uses SPSS 26 software for instrument testing, multiple linear regression analysis, and hypothesis testing. Based on the research results, it is known that product quality and service quality have a partially significant influence on customer satisfaction. Apart from that, it is also known that product quality and service quality simultaneously have a significant effect on customer satisfaction.